INTEGRASI BUDAYA ORGANISASI DAN PENGEMBANGAN KARIR DALAM LENSA EPIDEMIOLOGI MANAJERIAL: TINJAUAN LITERATUR MODEL KINERJA PEGAWAI RUMAH SAKIT MELALUI MEDIASI ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) PADA RSUD PRAYA LOMBOK TENGAH NTB - Lalu Iman Saptahadi (Jurnal Cakrawala Ilmiah, 2026)
Background: Hospital employee performance is a primary determinant of healthcare service quality. At RSUD Praya Central Lombok, HR management challenges require a strategic approach that integrates cultural aspects and career development. Objective: This study aims to analyze the impact of integrating organizational culture and career development on employee performance through the mediation of Organizational Citizenship Behavior (OCB) using a managerial epidemiology lens. Method: This research employs the Systematic Literature Review (SLR) method. The article selection process was conducted through Google Scholar and Scopus databases within the 2014-2024 timeframe. The analysis was performed on 8 primary journals meeting inclusion criteria related to hospital HR management. Results: Findings indicate that adaptive organizational culture and transparent career development systems significantly enhance OCB. OCB was found to act as a partial or full mediator bridging managerial variables to improved clinical and operational performance. The managerial epidemiology perspective confirms that intervention in organizational environmental factors (culture) is effective in reducing the risk of work inefficiency. Conclusion: Strengthening OCB through a conducive organizational climate is the key for RSUD Praya to achieve excellence in regional healthcare service performance.